Harry Potter and the structural biologist's (key)stone - Devos, Damien; Kalinina, Olga V.; Russell, Robert B. (Genome biology, 2006)
A report on the first European Keystone symposium 'Multi-protein complexes involved in cell regulation', Cambridge, UK, 18-23 August 2006.